Stress analysis due to internal explosion pressure of designed flameproof enclosure for hazardous area. Issue 2 (21st October 2019) - Ahirwal, Bhagirath; Prasad, Rashmi; Kashyap, Sudhir Kumar; Banerjee, Gautam
Abstract: Flameproof (Ex d) enclosures are constructed in such a way that an internal ignition of a flammable atmosphere will not be transmitted outside the enclosure and thereby preventing the ignition of surrounding flammables. The large Ex d enclosure was designed for gas group IIB explosive atmosphere with the help of MATLAB and ANSYS software and further a study of stress analysis due to internal pressure had been carried out on the plates and cover by keeping the thickness of body plate and cover constant. The study showed that stress was observed more in the center of the plate and reducing toward the edges of plates. The value of the length and breadth ratio (a/b) was found out with the help of the curve fitting method to calculate maximum stress (σmax ) in the designed Ex d enclosure. The calculated maximum stress of all the plates was less than the simulated results, so the simulated results indicated that the designed enclosure is within the safety limit and suitable for hazardous area.